Urban thirst: Exploring consumer dynamics and buying behaviour of soft drinks in Coimbatore city - Balaji, W; Samsai, T; Deepa, N; Parimalarangan, R; Patil, S G (Plant Science Today, 2025)
The soft drink market and industry are gaining importance due to growing awareness, rapid urbanization and changing lifestyles. This study aims to assess the consumer preference for soft drinks, analyse the factors influencing consumer buying behaviour and to identify the key constraints faced by consumers in purchasing soft drinks. The study considered key variables such as taste, price, health benefit, digestion, refreshment, convenience, flavour variety, brand image, packaging, size option, size option, lifestyle, consumption occasion, friend circle, peer influence and social media. These variables are selected for the study because they cover all the aspects, such as core sensory, brand influence, cultural and social interaction attributes. The research employs primary data collected through a well-structured questionnaire and secondary data from credible industry sources. The collected data were subjected to percentage analysis, factor analysis and the Garrett ranking techniques. Factor analysis extracted three major components that influenced buying behaviour, explaining a cumulative variance of 53.68 %. These included the essential satisfaction factor (23.59 %) comprising taste, price, health benefits, digestion, convenience, refreshment and flavour variety; the brand influence factor (17.91 %) including brand image, packaging, lifestyle, size option and consumption occasion; and the social interaction factor (12.19 %) involving peer influence, social media and friend circle. Garrett’s ranking technique revealed that the primary constraint faced by consumers are unhealthy (Garrett mean score: 69.68), followed by price sensitivity (59.45) and diet consciousness (56.60). The results show that consumers prefer a particular type of soft drink, with components like essential satisfaction and brand influence factors influencing the purchase decision more, major constraints like healthier options and price hinder the buying behaviour of consumers towards soft drinks. The study recommends that soft drink manufacturers and marketers prioritize health-based product innovation, competitive pricing and lifestyle-aligned branding strategies to meet the evolving preferences of urban consumers.